Envisioning nature, science, and religion - Proctor, James D., 1957- (West Conshohocken, Penn. : Templeton Press, 2009)
Contemporary scholarship has given rise to several different modes of understanding biophysical and human nature, each of which is entangled with related notions of science and religion. Envisioning Nature, Science, and Religion represents the culmination of three years of collaboration by an international group of fourteen natural scientists, social scientists, humanists, and theologians. The result is an intellectually stimulating volume that explores how the ideas of nature pertain to science and religion.
The nature of visions of nature : packages to be unpacked / Willem B. Drees -- Visions of nature through mathematical lenses / Douglas E. Norton -- Between apes and angels : at the borders of human nature / Johannes M.M.H. Thijssen -- Locating new visions / David N. Livingstone -- Enduring metaphysical impatience? / Robert E. Ulanowicz -- God from nature : evolution or emergence? / Barbara J. King -- Who needs emergence? / Gregory Peterson -- Creativity through emergence : a vision of nature and God / Antje Jackelén -- Rereading a landscape of atonement on an Aegean island / Martha L. Henderson -- The vision of malleable nature : a complex conversation / Andrew Lustig -- Visions of a source of wonder / Fred D. Ledley -- Nature as culture : the example of animal behavior and human morality / Nicolaas A. Rupke -- Environment after nature : time for a new vision / James D. Proctor -- Should the word nature be eliminated? / John Hedley Brooke.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Philosophy of nature -- Congresses; Religion and science -- Congresses; SCIENCE / Cosmology; Electronic books